Recovery of Cephalosporin Resistant Escherichia coli and Salmonella from Pork, Beef and Chicken Marketed in Nova Scotia. Issue 4 (1st August 2004) - Forward, Kevin R; Matheson, Katherine M; Hiltz, Margot; Musgrave, Heather; Poppe, Cornelius
Abstract : BACKGROUND: Antimicrobial use in farm animals is a potentially important contributor to the emergence of antimicrobial resistance. Resistant Salmonella may lead to serious human infections and resistant Escherichia coli may transfer plasmid-encoded resistance genes to other pathogens. OBJECTIVE: To determine the prevalence of E coli and Salmonella species resistant to the third generation of cephalosporins in retail meat products in Halifax, Nova Scotia in 2002. METHODS: Ground beef, ground pork and chicken wings were tested for E coli and Salmonella. E coli were selected on ceftriaxone-containing media. Beta-lactamases were characterised by isoelectric focusing, polymerase chain reaction and sequencing. Pulsed field gel electrophoresis was performed to determine the relationship of strains. The transferability of plasmids and location of resistance genes was also determined. RESULTS: Forty-three of 75 packages of chicken wings contained ceftriaxone-resistant E coli ; 42 of these contained beta-lactamases with isoelectric points at approximately 8.7. Six of seven CMY primer amplicons that were sequenced contained plasmid-mediated Citrobacter freundii-derived bla CMY-2; the other contained a CMY-2-like beta-lactamase. Pulsed field gel electrophoresis patterns demonstrated that strains were not clonal in nature. Four chicken samples contained Salmonella, one of which contained bla CMY-2-mediated resistance and an E coli bearing the same gene, but on different plasmids. Four of 100 beef samples contained bla CMY-2-bearing E coli ; none contained Salmonella . Two of 75 pork samples contained ceftriaxone resistant E coli, one of which encoded for CMY-2. One susceptible Salmonella strain was recovered from pork. CONCLUSIONS: Chicken from retail outlets located in Halifax, Nova Scotia, commonly contained bla CMY-2-bearing E coli . The relationship antibiotics used in food-producing animals and its effect on resistance of commensals and pathogens needs to be determined.